The impact of managerial change on performance: The role of team heterogeneity - Sandra Hentschel; Gerd Muehlheusser; Dirk Sliwka (Institute for the Study of Labor (IZA), 2012)
When a key responsibility of a manager is to allocate more or less attractive tasks to subordinates, these subordinates have an incentive to work hard and demonstrate their talents. As a new manager is less well acquainted with these talents this incentive mechanism is reinvigorated after a management change - but only when the team is sufficiently homogenous. Otherwise, a new manager quickly makes similar choices as the old one did. We investigate this hypothesis using a large data set on coach dismissals in the German football league where the selection of players is indeed a key task of the coach. Indeed, we find substantial evidence that coach replacements enhance team performance (only) in homogenous teams. Moreover, from a methodological point of view, we argue that there is typically a negative selection bias when evaluating succession effects, which might reconcile previous findings of no (or even negative) effects with the vast number of dismissals observed in reality.
Keywords: D22; J44; J63; 330; managerial succession; teams; heterogeneity; tournaments; Führungswechsel; Fußballsport; Arbeitsgruppe; Arbeitsleistung; Extensives Spiel; Deutschland